Inappropriate Metacognitive Status Increases State Anxiety in Genetic Counseling Clients - Shibata, Yuka; Matsushima, Masaaki; Takeuchi, Megumi; Kato, Momoko; Yabe, Ichiro (Frontiers in Psychology, 2022)
Background: Many genetic counseling (GC) studies have focused on anxiety status because clients of GC often feel anxious during their visits. Metacognition is known to be one of the causes of having an inappropriate thinking style. In this study, we examined the relationship between anxiety and the metacognitive status of GC clients according to their characteristics. Methods: The participants were 106 clients who attended their first GC session in our hospital from November 2018 to March 2021. The survey items were the clients’ characteristics, anxiety status at the time of the visit, and metacognitive status. Results: High state anxiety and high trait anxiety were observed in 34.9% and 11.3% of clients, respectively. Clients who were a relative or had a family history were significantly more likely to have high state anxiety. As for metacognitive status, only negative beliefs about thoughts concerning uncontrollability and danger were associated with having an anxiety status. Furthermore, multivariate analysis showed that negative beliefs about thoughts concerning uncontrollability and danger were an independent determinant of higher state anxiety, but not being a relative or having a family history. Metacognitive status scores were significantly lower in clients than in the control group. Conclusion: State anxiety was shown to be more dependent on the negative beliefs about thoughts concerning uncontrollability and danger of GC clients than their characteristics. The results of this study will contribute to the development of new GC psychosocial support measures to address the anxiety of GC clients.